Nature of delay in nominated subcontracting - Nasid Masrom, Md. Asrul (2007)
Construction delay is a results of occurrence beyond the control of either the contractor or the employer. Delay can be categorized as excusable, non-excusable, compensable and concurrent. There are many causes that can contribute delay in construction. However, delay in nominated subcontracting are very seldom acknowledged and the ways to improve also seldom discussed. As a result, to identify the causes of delay on account of nominated subcontractor’s work are often difficult. Thus, the objective of this study is to identify circumstances which are caused delay in nominated subcontractor’s work and their implication to the main contractor. In Malaysia, most of the standard form of contract such as PWD203A, PAM 19988 and CIDB 2000 have provided grounds which gives entitlement for an extension of time to the main contractor in the event of delay on the part of the nominated subcontractor. The methodology that has been applied in this study is a detail analysis of ten (10) cases which have been selected through Malayan Law Journal. The results proved that there are several circumstances which caused delay in nominated subcontractor’s work. Every causes have their own implication to the main contractor in terms of entitlement of extension of time as well as the liability of damages. This study concludes that, irregular payment is the prominent cause which contributed to delay in nominated subcontracting.